FG-4592 relieves diabetic kidney disease severity by influencing metabolic profiles via gut microbiota reconstruction in both human and mouse models - Jiang, Yumin; Cui, Wen; Zhang, Yiding; Wang, Ting; Zheng, Xuejun; Li, Huangmin; Shang, Jin (Frontiers in Physiology, 2023)
Objective Diabetic kidney disease (DKD) is one of the most prevalent complications of diabetes mellitus (DM) and is highly associated with devastating outcomes.Hypoxia-inducible factor (HIF), the main transcription factor that regulates the cellular responses to hypoxia, plays an important role in regulating synthesis of erythropoietin (EPO). FG-4592 is the HIF stabilizer which is widely used in the patients with renal anemia. We aim to investigate the effect of FG-4592 on DKD phenotypes and pharmacologic mechanism from the perspective of gut microbiota and systemic metabolism.The clinical data of 73 participants including 40 DKD patients combined renal anemia treated with FG-4592 and 33 clinical indices-matched DKD patients without FG-4592 treatment from the First Affiliated Hospital of Zhengzhou University were collected at the beginning and after 3-6 months follow-up period. We established DKD mouse models treated by FG-4592 and performed fecal microbiota transplantation from FG-4592 treated DKD mice to investigate the effects of FG-4592 on DKD and to decipher such mechanism from microbial perspective. Untargeted metabolome-microbiome combined analysis was implemented to globally delineate the mechanism of FG-4592 from both microbial and metabolomic aspects. Result DKD phenotypes were significantly improved after 3-6 months FG-4592 treatment in DKD patients combined with renal anemia, including decreased level of systolic blood pressure, serum creatinine and increased estimated glomerular infiltration rate. Such effects were also achieved in DKD mouse model treated with FG-4592 and can be also induced by FG-4592 influenced gut microbiota. Untargeted plasma metabolomics-gut microbiota analysis showed FG-4592 dramatically alters both microbial and metabolic profiles of DKD mice and relieves DKD phenotypes via upregulating beneficial gut microbiota-associated metabolites. Conclusion FG-4592 can globally relieve the symptoms of DKD patients combined with renal anemia. In animal experiment, FG-4592 can reconstruct intestinal microbial profiles of DKD to further upregulate the production of gut-associated beneficial metabolites, subsequently improve DKD phenotypes.